(untitled) (Web of Teachers: Inderscience Research, 2025)
In this article, we conducted a linguistic analysis of advertising texts in the economic life of Uzbekistan. In the article, we studied the economic aspects of the language of advertising, analyzing what economic goals advertising texts serve in terms of language and meaning, and what linguistic techniques are used to advertise goods or services, and expressed our scientific views on this matter.